Molecular detection OF Mycoplasma haemofelis in cats in selected districts in Kelantan - Subashini Ratha Pukallenthy (2022)
This research is aimed to detect the presence of Mycoplasma haemofelis infection in cats in Kota Bharu and Bachok, Kelantan, Malaysia, using molecular method. Samples were collected from 18 household cats after obtaining consent from the Faculty of Veterinary Medicine at Universiti Malaysia Kelantan (UMK) and the Final Year Project (FYP) Committee (UMK/FPV/ACUE/FYP/003/2022). Whole blood samples were collected and then analysed using Polymerase Chain Reaction (PCR). In conclusion, the outcome of this research was all negative for all the 18 blood samples that was collected indicating that the household cats in Kota Bharu and Bachok, Kelantan are not infected with Mycoplasma haemofelis. This result was supported by absence of expected bands from the samples other than the positive control. Keywords: Mycoplasma haemofelis, cats, whole blood, Polymerase Chain Reaction